Urgensi Pedagogik dalam Pembelajaran dan Implikasinya dalam Pendidikan - Rahman, Abdul (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2018)
An educator must have an understanding of pedagogical learning. Understanding of pedagogic aims to make children later in life able to understand and live life and later can support themselves, can live meaningfully, and can also glorify life. The lack of understanding of teachers and educators about the meaning of fundamental change in teaching, educating and learning, keeps them insistent on educational pracces built on old rules, rules that are never renewed by new demands arising in society. In order for the educated participants to understand and master a number of important knowledge in life, to master certain skills, and to understand the values of life, first taught through knowledge learning, the second is taught through practice of mastering real skills, and the third is taught through an understanding of the values of life